Accessibility and Utilisation of Maternal Health Services by Migrant Female Head Porters in Accra. - Yiran, G-S.A.; Teye, J.K.; Yiran, G.A.B. (Springer, 2015)
Accessibility to maternal health care by marginalised groups, such as poor migrant women, has remained an issue of concern in Ghana. While a number of studies have been conducted on the livelihoods of migrant female head porters (Kayayei) in cities in Southern Ghana, there is little understanding of their accessibility and utilisation of maternal health services. This paper examines the challenges that the migrant female head porters encounter in the process of seeking maternal health care in Accra. The data were collected through a questionnaire survey on a sample of 70 female head porters and in-depth interviews with key informants and some of the Kayayei. The findings indicate that the factors affecting accessibility to maternal health services by the Kayayei are unavailability of health facilities in the slums where Kayayei live, low-income levels, high cost of maternal health care, long queues and waiting times at modern health facilities, and the perception that traditional medicines are adequate for protecting pregnant women and their babies. It was therefore suggested that government should increase the number of health facilities and strengthen the National Health Insurance Scheme to enhance access to health care by this vulnerable and poor group of people as well as increase health educational campaigns
Journal Article
Keywords: Maternal health care; Migrant head porters; Health financing; Reproductive health